2009
DOI: 10.1007/s10517-010-0801-y
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Changes in Paraurethral Area after Introduction of Tissue Engineering Construct on the Basis of Adipose Tissue Stromal Cells

Abstract: We studied morphological changes in the paraurethral area of Wistar rats after introduction of tissue engineering constructs on the basis of multipotent mesenchymal stem cells and gelatin sponge. The tissue engineering construct containing autologous culture of the stromal fraction of the adipose tissue was most effective. After introduction of this construct we observed more rapid degradation of the construct matrix and more intensive formation of collagen fibers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Adipocytes constitute almost 90% of adipose tissue volume and nearly 65% of the total cell number [6]. Stem cells isolated from lipoaspirates have demonstrated a broad in vitro adipogenic, chondrogenic, osteogenic, and myogenic lineage commitment [7], [8] as well as differentiation into pancreatic cells, hepatocytes, and neurogenic cells [9], [10], [11]. ASCs (adipose-derived stem cells) are a plastic-adherent, multipotent stem cell population, which display a similar differentiation potential to other MSCs, and the ability to differentiate into cells of several lineages from all three germinal layers [12].…”
Section: Introductionmentioning
confidence: 99%
“…Adipocytes constitute almost 90% of adipose tissue volume and nearly 65% of the total cell number [6]. Stem cells isolated from lipoaspirates have demonstrated a broad in vitro adipogenic, chondrogenic, osteogenic, and myogenic lineage commitment [7], [8] as well as differentiation into pancreatic cells, hepatocytes, and neurogenic cells [9], [10], [11]. ASCs (adipose-derived stem cells) are a plastic-adherent, multipotent stem cell population, which display a similar differentiation potential to other MSCs, and the ability to differentiate into cells of several lineages from all three germinal layers [12].…”
Section: Introductionmentioning
confidence: 99%
“…Fat is an active and dynamic tissue composed of several different cell types, including adipocytes, fibroblasts, smooth muscle cells, endothelial cells, and adipogenic progenitor cells called pre-adipocytes [30], [31], [32]. Stem cells isolated from lipoaspirates have demonstrated a broad in vitro adipogenic, chondrogenic, osteogenic, and myogenic lineage commitment [33], [34] as well as differentiation into pancreatic cells, hepatocytes, and neurogenic cells [35], [36], [37]. Cytometric analysis of adipose-derived stem cells (ASCs) has shown that these cells do not express CD31 and CD45, but do express CD34, CD73, CD105, and the mesenchymal stem cell marker CD90 [38], [39].…”
Section: Efficacy Of Lipofillingmentioning
confidence: 99%
“…Fat is an active and dynamic tissue composed of several different cell types, including adipocytes, fibroblasts, smooth muscle cells, endothelial cells, and adipogenic progenitor cells called pre-adipocytes [2] , [3] , [4] , [5] . Stem cells isolated from lipoaspirates have demonstrated broad in vitro adipogenic, chondrogenic, osteogenic, and myogenic lineage commitment [6] , [7] as well as the ability to differentiate into pancreatic cells, hepatocytes, and neurogenic cells [8] , [9] , [10] . Cytometric analysis of adipose-derived stem cells (ASCs) has shown that these cells do not express CD31 and CD45, but express CD34, CD73, CD105, and the mesenchymal stem cell marker CD90 [11] , [12] .…”
Section: Introductionmentioning
confidence: 99%